2021 IEEE International Conference on Multimedia and Expo (ICME) 2021
DOI: 10.1109/icme51207.2021.9428470
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time H.266/VVC Software Decoder

Abstract: The new Versatile Video Coding Standard (VVC) was finalized in July 2020. This new international standard is able to provide a higher compression efficiency by up to 50% for the same subjective quality compared to its predecessor HEVC but at the cost of an increased computational load. This paper investigates the complexity of VVC decoder processing blocks and presents a highly optimized decoder implementation that can achieve 4K 60fps VVC real-time decoding on an x86 based CPU using SIMD instruction extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Within a few months after the VVC standard was finalized, Fraunhofer HHI made their optimized Versatile Video Decoder (i.e., VVdeC) available on GitHub [73], [74]. Tencent also presented an independently developed VVC decoder (i.e., O266dec) [75] which was implemented from scratch and runs on multiple operating systems including Linux, Microsoft Windows, Apple Mac OSX, iOS and Android [76]. Alibaba demonstrated Ali266, a thin VVC decoder that runs efficiently on mobile phones of wide-ranging hardware capabilities [72].…”
Section: B Optimized Vvc Decodersmentioning
confidence: 99%
See 3 more Smart Citations
“…Within a few months after the VVC standard was finalized, Fraunhofer HHI made their optimized Versatile Video Decoder (i.e., VVdeC) available on GitHub [73], [74]. Tencent also presented an independently developed VVC decoder (i.e., O266dec) [75] which was implemented from scratch and runs on multiple operating systems including Linux, Microsoft Windows, Apple Mac OSX, iOS and Android [76]. Alibaba demonstrated Ali266, a thin VVC decoder that runs efficiently on mobile phones of wide-ranging hardware capabilities [72].…”
Section: B Optimized Vvc Decodersmentioning
confidence: 99%
“…They both aim at enabling live decoding of 4K video on modern x86 processors by incorporating:  Single-instruction multiple data (SIMD) architecture optimization of sample operations using instruction sets such as SSE42, AVX2 and AVX512, where applicable. It is observed that this optimization is specifically beneficial for the inverse transforms, motion compensation interpolation, and in-loop filters [73], [75].  Multi-threading at the picture level, CTU level, task level and sub-CTU level.…”
Section: B Optimized Vvc Decodersmentioning
confidence: 99%
See 2 more Smart Citations
“…Measured in terms of runtime, in the commonly used random access configuration, VVC software test model VTM takes around 8× more time to encode and 2× more to decode than the HEVC software test model, HM [5]. First reports of optimized implementations including real-time decoder implementations [6][7][8] and optimized encoding algorithms [9][10][11][12][13] are available with very improved runtime. Those indicate that the VVC complexity, and its complexity increase when compared to HEVC, can only in limited manner be measured when comparing the reference software runtimes.…”
Section: Introductionmentioning
confidence: 99%